Evaluation and Study of Minerals from Leea macrophylla Roxb (Leeaceae) - Jadhao, K.D.; Wadekar, M.P. (Asian Journal of Chemistry, 2010)
Leea macrophylla Roxb is a wild edible plant. The plant material was collected from Melghat (Maharashtra) for analysis of moisture and minerals content. Minerals are very essential nutrient for human life and whole plant of Leea macrophylla is helpful in nutritional point of view. It also fulfill our daily requirements of food. The powder of L. macrophylla. root with clarified butter was prescribed in morning as age sustainer. The only sun dried plant materials was used for estimation of minerals like sodium, potassium and calcium was done by flame photometer at 5lb pressure while sulphur, boron and iron was estimated by spectrophotometer. Hence, for fulfillment of minerals requirement of human body the whole plant material is useful.